Determinants of post-stroke depression among stroke survivors at University of Gondar Hospital, Northwest Ethiopia: a case-control study - Fantu, Ephrem; Hailu, Workagegnehu; Bekele, Nebiyu; Tsegaye, Tewodros; Tadesse, Melaku; Asres, Mezgebu Silamsaw (BMC neurology, 2022)
Background Stroke is one of the most common causes of disability among adults. Post-stroke depression (PSD) is a frequent neuropsychiatric complication in stroke patients. Despite the increasing prevalence of stroke, there is a paucity of data on PSD and its determinants among stroke survivors in developing countries like Ethiopia. We aim to assess the factors associated with PSD in survivors of stroke. Method A hospital-based unmatched case-control study was conducted during the period of February to July 2020 at University of Gondar Hospital among stroke survivors. Study subjects were recruited consecutively. Socio-demographic and clinical data were obtained from patients’ interviews and medical record reviews. A diagnosis of PSD was made using the Patient Health Questionnaire (PHQ-9). EpiData version 3.1 was used to enter data, and SPSS version 26 was used to analyze it. Bivariate and multivariate logistic regressions were fitted to identify associated variables. The adjusted odds ratio (AOR) with 95% confidence interval (CI) and p -value 0.05 were used to determine the significance of the association. Result A total of 240 stroke survivors were included in the study (80 cases and 160 controls). The mean age was 60.8 years (SD ± 14.3) with an equal sex distribution. Variables statistically associated with PSD were male gender (AOR = 3.5, 95% CI: 1.64-7.46 C, P -value = 0.001), subcortical location of the largest lesion (AOR = 2.42, 95% CI: 1.06–5.56, p -value = 0.036), severity of the stroke (AOR = 52.34, 95% CI:10.64-256.87, p -value = 0.000), physical disability (AOR = 5.85. 95% CI:1.94–17.65, p -value = 0.002), previous history of stroke or transient ischemic attack (AOR = 5.90, 95% CI:2.04–17.10, p -value = 0.001) and ischemic heart disease (AOR = 9.97, 95% CI:3.4-29.22, p -value = 0.000). Conclusion Important factors in the occurrence of PSD in this study include prior history of stroke, physical disability, severity of the stroke, subcortical location of the lesion, male gender, and ischemic heart disease. Stroke patients with such factors need routine screening for PSD, particularly in LMICs where there is uncoordinated post-stroke care, a shortage of neurologists and mental health practitioners.